Review: Determining Factors in the Pelletization of Coffee Grounds as Solid Biofuel - Ana Cecilia Revelo Rodríguez; María Teresa Cotes Palomino; Carmen Martínez García; Ana B. López (Circular Economy and Sustainability, 2026)
The growing demand for pellets as a renewable energy source reflects the global need to reduce dependence on fossil fuels and promote more sustainable production models. Despite recent challenges, such as rising production costs and raw materials shortages, the pellet industry has maintained steady growth, highlighting the role of the circular economy in resource optimization and waste reduction. In this context, the exploration of new biomass sources for pellet production is presented as a key strategy, including agricultural, forestry and agri-food waste. Coffee, the second most consumed beverage worldwide, generates large volumes of organic waste, whose inadequate management represents a significant environmental problem. In particular, spent coffee grounds (SCG) have a high moisture content ( $$\sim$$ 70%) and organic compounds, which facilitates the generation of pollutant emissions and increases the risk of spontaneous combustion, underscoring the need for valorization strategies. The main objective of this research is to evaluate the potential of SCG as a raw material for pellet production by analyzing its physicochemical properties, its behavior during the pelletization process and its classification according to ISO 17225–6:2021 standards for non-woody pellets. Integrating these residues into solid biofuel production, along with optimizing densification parameters, could provide an innovative and viable alternative aligned with the principles of the circular economy, contributing to waste reduction and the development of more sustainable energy sources.

Lightweight artificial aggregates from ornamental rock cutting sludge and aggregate washing sludge: raw material for sustainable construction and agriculture - María Teresa Cotes-Palomino; Jacinto Alonso-Azcárate; Antonio Conde-Sánchez; Alejandro Dubbelman Vizcaíno; Ana B. López; Carmen Martínez-García; Ana M. Martínez-Rodríguez; Ana Cecilia Revelo Rodríguez; Francisco José Troyano Pérez; Carlos Javier Cobo-Ceacero (Environmental Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Survival of epithelial ovarian cancer in Black women: a society to cell approach in the African American cancer epidemiology study (AACES) - Joellen M. Schildkraut; Courtney Johnson; Lauren F. Dempsey; Bo Qin; Paul Terry; Maxwell Akonde; Edward S. Peters; Hannah Mandle; Michele L. Cote; Lauren Peres; Patricia Moorman; Ann G. Schwartz; et al. (Cancer Causes & Control, 2023)
Purpose The causes for the survival disparity among Black women with epithelial ovarian cancer (EOC) are likely multi-factorial. Here we describe the African American Cancer Epidemiology Study (AACES), the largest cohort of Black women with EOC. Methods AACES phase 2 (enrolled 2020 onward) is a multi-site, population-based study focused on overall survival (OS) of EOC. Rapid case ascertainment is used in ongoing patient recruitment in eight U.S. states, both northern and southern. Data collection is composed of a survey, biospecimens, and medical record abstraction. Results characterizing the survival experience of the phase 1 study population (enrolled 2010–2015) are presented. Results Thus far, ~ 650 patients with EOC have been enrolled in the AACES. The five-year OS of AACES participants approximates those of Black women in the Surveillance Epidemiology and End Results (SEER) registry who survive at least 10-month past diagnosis and is worse compared to white women in SEER, 49 vs. 60%, respectively. A high proportion of women in AACES have low levels of household income (45% < $25,000 annually), education (51% ≤ high school education), and insurance coverage (32% uninsured or Medicaid). Those followed annually differ from those without follow-up with higher levels of localized disease (28 vs 24%) and higher levels of optimal debulking status (73 vs 67%). Conclusion AACES is well positioned to evaluate the contribution of social determinants of health to the poor survival of Black women with EOC and advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women.

Alcohol intake and risk of pituitary adenoma - David J. Cote; Timothy R. Smith; Ursula B. Kaiser; Edward R. Laws; Meir J. Stampfer (Cancer Causes & Control, 2022)

Sex-dependent personality in two invasive species of mosquitofish - Marcus Michelangeli; Julien Cote; David G. Chapple; Andrew Sih; Tomas Brodin; Sean Fogarty; Michael G. Bertram; Jack Eades; Bob B. M. Wong (Biological Invasions, 2020)

Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

A perspective on climate-resilient development and national adaptation planning based on USAID's experience - Yoon Kim; Joel B. Smith; Charlotte Mack; Jonathan Cook; John Furlow; Joyce-Lynn Njinga; Michael Cote (Climate and Development, 2017)

The effect of resident vegetation cover on abundance and diversity of green lacewings (Neuroptera: Chrysopidae) on olive trees - Mario Porcel; B. Cotes; J. Castro; M. Campos (Journal of Pest Science, 2017)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Stretched-grid Model Intercomparison Project: decadal regional climate simulations with enhanced variable and uniform-resolution GCMs - M. Fox-Rabinovitz; J. Cote; B. Dugas; M. Deque; J. L. McGregor; A. Belochitski (Meteorology and Atmospheric Physics, 2008)

Habitat use and early winter movements by juvenile Atlantic cod in a coastal area of Newfoundland - D. Cote; S. Moulton; P. C. B. Frampton; D. A. Scruton; R. S. McKinley (Journal of Fish Biology, 2004)
Acoustic telemetry was used to monitor the movements and landscape scale habitat use of age 2–3 year juvenile Atlantic cod Gadus morhua in Newman Sound, a coastal fjord of Newfoundland, during late autumn and early winter (24 October 1999 to 22 January 2000). Substratum, bathymetric relief and depth use were studied to determine if it differed from the pattern expected given an absence of selectivity (habitat use proportional to habitat availability). Prior to winter migrations, most Atlantic cod maintained small home ranges (0·5–33·4 ha, median = 2·1 ha) although a few individuals moved more widely. No relationship between total length ( L T ) and home range size was detected. In Inner Newman Sound, Atlantic cod occupied depths of 10–29 m more than expected given availability, while depths of 0–9 and 40–59 m were underutilized. No significant relationship between depth and L T was detected. Areas of medium (5–10%) or high (>10%) bathymetric relief and boulder or kelp habitats were used significantly more than expected given the availability of these habitats. Sand and eelgrass substrata were underutilized given availability, although many Atlantic cod used sandy‐bottomed areas to some degree. Flexibility in habitat use by the individuals that were studied suggested reduced predation risk relative to younger conspecifics. Winter migrations to deeper water beyond Newman Sound began in mid‐November, coinciding with the disappearance of the thermocline, and continued until 27 December. Approximately 30% of monitored individuals did not migrate and maintained their home ranges into the winter season. No significant differences in L T between migrating and resident groups were detected, however, the condition of migrating fish was significantly higher than in resident fish. This finding supports the theory that feeding history plays a role in the decision to undertake migration.

Analysis of soil wetting and solute transport in subsurface trickle irrigation - Claire M. Cote; Keith L. Bristow; Philip B. Charlesworth; Freeman J. Cook; Peter J. Thorburn (Irrigation Science, 2003)

Fluctuations of Climatic Conditions, Elemental Cycling and Forest Growth at the Watershed Scale - F. Courchesne; A. G. Roy; P. M. Biron; B. Cote; J. Fyles; W. H. Hendershot (Environmental Monitoring and Assessment, 2001)

Does erythrocyte infusion improve 3.2-km run performance at high altitude? - Kent B. Pandolf; Andrew J. Young; Michael N. Sawka; James L. Kenney; Mark W. Sharp; Randy R. Cote; Beau J. Freund; C. Robert Valeri (European Journal of Applied Physiology, 1998)